Postpartum vertebral artery dissection: case report and review of the literature - Manasewitsch, Nicholas T. (Thromb J, 2020)
BACKGROUND: Hypertensive disorders of pregnancy are associated with vascular complications, including ischemic stroke and cervical artery dissection. Vertebral artery dissection (VAD), however, is rare. We describe a 31-year-old female who presented with vertigo, nausea, and vomiting and was found to have a VAD. In addition, we discuss the presentation, differential diagnosis, and pathogenesis of this uncommon but clinically significant vascular event and summarize other cases of vertebral artery dissection described in the medical literature. CASE PRESENTATION: A 31-year-old Hispanic woman presented 10 days postpartum with a one-day history of vertigo, nausea, vomiting, and frontal headache. The patient’s pregnancy course had been complicated by preeclampsia, chorioamnionitis, and iron-deficiency anemia, and her delivery was complicated by acute hemorrhage. Physical examination was significant for left leg ataxia. Laboratory studies showed marked thrombocytosis. Emergent computed tomography (CT) scan of the head was obtained and revealed a left cerebellar ischemic large vessel stroke. Subsequent CT angiography of the head and neck showed a left VAD. Based on correlation of the clinical history and laboratory and imaging findings, a diagnosis of vertebral artery dissection secondary to reactive (secondary) thrombocytosis from overlapping iron-deficiency anemia and acute hemorrhage was established. The patient was started on a heparin infusion and experienced significant improvement after a four-day hospitalization. CONCLUSION: VAD is a rare but important cause of neurologic symptoms in the postpartum period and should be considered in the differential diagnosis for women who present with headache and/or vertigo. Women aged 30 years or older and those with a history of a hypertensive disorder of pregnancy are at particularly high risk. Prompt diagnosis and management of VAD is essential to ensure favorable outcomes.